2021
DOI: 10.3390/en14165018
|View full text |Cite
|
Sign up to set email alerts
|

Fuel Cell Electric Vehicle (FCEV) Energy Flow Analysis in Real Driving Conditions (RDC)

Abstract: The search for fossil fuels substitutes forces the use of new propulsion technologies applied to means of transportation. Already widespread, hybrid vehicles are beginning to share the market with hydrogen-powered propulsion systems. These systems are fuel cells or internal combustion engines powered by hydrogen fuel. In this context, road tests of a hydrogen fuel cell drive were conducted under typical traffic conditions according to the requirements of the RDE test. As a result of the carried-out work, energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Sci. Technol., 11(2) 114-127 August 2022 doi: 10.13170/aijst.11.2.24592 Copyright: © 2022 by Aceh International Journal of Science and Technology 124 fuel cell in the vehicle's propulsion is more than 3 times that contributed by the battery in urban condition and even reach 28 times on highway condition (Szałek et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Sci. Technol., 11(2) 114-127 August 2022 doi: 10.13170/aijst.11.2.24592 Copyright: © 2022 by Aceh International Journal of Science and Technology 124 fuel cell in the vehicle's propulsion is more than 3 times that contributed by the battery in urban condition and even reach 28 times on highway condition (Szałek et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The authors carried out earlier research on the analyzed drive type only using the first version of the Toyota Mirai drive system [34]. These studies showed a low degree of hybridization, as the fuel cells held over 70% of all available energy.…”
Section: Fuel Cell Testing For Automotive Applicationsmentioning
confidence: 99%
“…The remaining 4% is produced by electrolysis of water. (Szałek et al, 2021). However, with the recent industrial-scale concept of producing green hydrogen offshore by deploying electrolyser systems on rebuilt oil rigs, this structure may change.…”
Section: Introductionmentioning
confidence: 99%